The Influence of Transformational Leadership and Competence on the Work Performance of TNI AU Finance Officers - Wisnu Wicaksono (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to examine the influence of transformational leadership and competence on the work performance of TNI AU financial officers. The formulation of the problem raised in this study includes three main aspects: (a) the partial influence of transformational leadership on work performance, (b) the partial influence of competence on work performance, and (c) the simultaneous influence of transformational leadership and competence on the work performance of TNI AU financial officers. The research method used is an associative quantitative approach. This study uses a survey with a questionnaire as a data collection instrument, which is then analyzed using SPSS statistical software version 25. The research population is all TNI AU finance officers, with a sample of 99 people who are randomly selected. Data analysis was carried out through a linear regression test to test the partial and simultaneous influence of independent variables (transformational leadership and competence) on bound variables (work performance). The results of the study show that transformational leadership and competence partially have a positive and significant influence on work performance. Simultaneously, these two variables have also been proven to have a significant effect on work performance, with a contribution of 51.6% to the variation in the work performance of TNI AU finance officers. The discussion of these results emphasizes the importance of developing inspirational leadership and high competence in achieving optimal performance in the military environment.